Surface air temperature measured at the Argentinean–German Geodetic Observatory (AGGO) in 2018 - Pablo Luis Antico; José Vera; Alfredo Pasquaré; Romina Galván; Michael Häfner; Mauricio Gende; Claudio Brunini; Andreas Güntner; Stephan Schröder (PANGAEA, 2023)
Surface air temperature measurements obtained from different sensors are used to construct a unique time series with one minute time-interval. Apart from differences in design and environmental exposition, periods of missing data also exist in the data series of each sensor. A primary data set was selected in terms of quality and temporal extension. A combination of two different techniques is applied to complete this data set: one is based on the autocorrelation of the series and the other on measurements taken from other sensors. The resulting values constitute a complete series of surface air temperature at AGGO.
In: Antico, PL et al. (2023): Surface air temperature measured at the Argentinean–German Geodetic Observatory (AGGO), 2018-2021 [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.954612